Pengaruh Audit Tenure dan Auditor Switching terhadap Kualitas Audit pada Perusahaan Manufaktur di Indonesia dengan Financial Distress sebagai Pemoderasi - Dede Elevendra; Nayang Helmayunita (Universitas Negeri Padang, 2021)
The purpose of this study was to determine the effect of audit tenure and auditor switching on audit quality with financial distress as a moderating variable. The analysis of this research used logistic regression analysis. The sample consists of companies listed on the Indonesia Stock Exchange (BEI) for the current year (2015-2019). The results showed that audit tenure and auditor switching had no effect on audit quality and financial distress was unable to moderate the effect of audit tenure and auditor switching on audit quality.